The effect of personality traits on consumer behaviour among football fans: The mediating role of fan loyalty - Hakan Akgül; Can Özgider; İlhan Adiloğulları (PLoS ONE, 2026)
The aim of the current study was to examine the impact of personality traits on consumer behaviour among football fans in a Turkish setting by focusing on the mediating role of sports fans’ loyalty. Drawing on the Social Identity Theory, this research examines how the Big Five Personality characteristics, including openness, agreeableness, conscientiousness, extraversion, and emotional stability, influence sports consumption through loyalty mechanisms. Data were gathered from 929 active university students who were all active football fans by using three validated scales for personality, fan loyalty, and consumption behaviour. The indirect effects of personality traits on consumer behaviour through fan loyalty were significant, whereas the direct effects were not statistically significant. Besides, the results indicate that personality traits are associated with sports fan consumption patterns through fan loyalty. This highlights fan loyalty as a potential mechanism linking individual characteristics with collective behaviour patterns. Furthermore, the findings shed light on our understanding of sports fan engagement by combining perspectives from personality theory and social identity theory. Ultimately, it offers practical implications for both sports marketers and club managers seeking ways to foster long-term relationships with their fans, particularly within collectivist cultures.